Fluoroquinolones versus trimethoprim-sulfamethoxazole for the treatment of Stenotrophomonas maltophilia infections: a systematic review and meta-analysis. (May 2019) - Ko, J.-H.; Kang, C.-I.; Cornejo-Juárez, P.; Yeh, K.-M.; Wang, C.-H.; Cho, S.Y.; Gözel, M.G.; Kim, S.-H.; Hsueh, P.-R.; Sekiya, N.; Matsumura, Y.; Lee, D.-G.; et al.
Abstract: Background: Fluoroquinolones are a popular alternative to trimethoprim-sulfamethoxazole for Stenotrophomonas maltophilia infections. Objectives: To compare the effects of fluoroquinolones and trimethoprim-sulfamethoxazole on mortality of S. maltophilia infections. Data sources: PubMed and EMBASE. Study eligibility criteria: Clinical studies reporting mortality outcomes of S. maltophilia infections. Participants: Patients with clinical infections caused by S. maltophilia. Interventions: Fluoroquinolone monotherapy in comparison with trimethoprim-sulfamethoxazole monotherapy. Methods: Systematic review with meta-analysis technique. Results: Seven retrospective cohort and seven case–control studies were included. Three cohort studies were designed to compare the two drugs, whereas others had other purposes. A total of 663 patients were identified, 332 of which were treated with trimethoprim-sulfamethoxazole (50.1%) and 331 with fluoroquinolones (49.9%). Three cohort studies were designed to compare the effect of the two drugs, whereas the others had other purposes. Levofloxacin was most frequently used among fluoroquinolones (187/331, 56.5%), followed by ciprofloxacin (114/331, 34.4%). The overall mortality rate was 29.6%. Using pooled ORs for the mortality of each study, fluoroquinolone treatment (OR 0.62, 95% CI 0.39–0.99) was associated with survival benefit over trimethoprim-sulfamethoxazole treatment, with low heterogeneity ( I 2  = 18%). Specific fluoroquinolones such as ciprofloxacin (OR 0.44, 95% CI 0.17–1.12) and levofloxacin (OR 0.78, 95% CI 0.48–1.26) did not show a significant difference in comparison with trimethoprim-sulfamethoxazole. In the sub-group analyses of adult and bacteraemic patients, significant differences in mortality were not observed between fluoroquinolones and trimethoprim-sulfamethoxazole. Conclusions: Based on a meta-analysis of non-randomized studies, fluoroquinolones demonstrated comparable effects on mortality of S. maltophilia infection to trimethoprim-sulfamethoxazole, supporting the use of fluoroquinolones in clinical S. maltophilia infections. Although the pooled analysis of overall studies favoured fluoroquinolones over trimethoprim-sulfamethoxazole, the studies included were observational, and sub-group analyses of certain fluoroquinolone agents did not show statistical differences with trimethoprim-sulfamethoxazole. Randomized clinical studies are needed to address these issues. Graphical abstract: Image 1